Sistem Informasi Manajemen Karyawan Freelance Berbasis Web dengan Notifikasi Real-Time pada Event Organizer - Syams Kurniawan Hidayat; Riyan Abdul Aziz; Adnan Terry Susesno (J-Innovation, 2026)
Managing freelance employees in Event Organizer activities presents challenges in scheduling, task assignment, communication, and the delivery of dynamic information. Manual management processes often lead to delays in information dissemination and coordination errors between event managers and freelance workers. This study develops a web-based Freelance Employee Management Information System equipped with real-time notification features to support employee data management, event management, task assignment, scheduling, and communication. The system was developed using web technologies with WebSocket implemented as a mechanism for delivering notifications directly to users. The system architecture adopts a three-tier approach consisting of the frontend, backend, and database. Functional testing results showed that the system met all functional requirements with a 100% success rate, while WebSocket testing achieved an average notification latency of 48.7 ms. These results demonstrate that the proposed system effectively supports structured freelance employee management and enables faster and more efficient information delivery in Event Organizer operations